Method for preparing core-shell structure metal matrix composite powder through electrostatic self-assembly

Through the combination of electrostatic self-assembly technology and solid-liquid fluidized bed, the uniform distribution of the clad powder on the surface of the metal powder is achieved, and the problems of uneven distribution of powder and easy structure are solved, and a high structural integrity is prepared Core-shell structure metal-based composite powder with low impurity content.

CN119489187AActive Publication Date: 2025-02-21INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311041705.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

In existing powder metallurgy or 3D printed powders, alloy element powders and reinforced phases have problems such as uneven distribution, easy agglomeration and easy destruction of reinforced phase structures, resulting in uneven distribution of the cladding powder on the surface of the metal powder.

Method used

The electrostatic self-assembly technology is used to combine the solid-liquid fluidized bed, and the clad powder is modified by surfactant, so that it can contact and combine with the metal powder in the fluidized bed to achieve uniform distribution of the clad powder.

Benefits of technology

The prepared core-shell structure metal-based composite powder has the advantages of high structural integrity of metal powder, uniform distribution of coating powder and low impurity content, which solves the advantages of low powder integrity and easy damage to the coating powder structure and Impurity pollution problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489187A_ABST
    Figure CN119489187A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing core-shell structure metal-based composite powder through electrostatic self-assembly, which comprises the following steps: (1) modifying coating layer powder through a surfactant to enable the surface of the coating layer powder to have charges opposite to those of metal powder, so as to obtain dispersed coating layer powder dispersion liquid; and (2) the coating layer powder dispersion liquid is placed in a solid-liquid fluidized bed, the liquid is made to be in a fluidized state, metal powder is added into the fluidized bed, the surface of the metal powder is evenly coated with a coating material through electrostatic self-assembly, the fluidization time is 5-240 min, and after fluidization, the core-shell structure metal-based composite powder is cleaned, dried and packaged for use. The composite powder with uniform coating layer distribution and controllable content is synthesized by changing the surface charge distribution of different powder to enable the powder and metal powder to have opposite charges and combining the characteristic of special flow distribution of the solid-liquid fluidized bed, and meanwhile, the method has the advantages of simple process, low cost, short flow, easiness in realizing large-scale production and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of raw material preparation of metal-based composite materials, and specifically relates to a powder raw material preparation technology for high-performance metal-based composite materials in the field of powder metallurgy or 3D printing, and more specifically to a method for preparing core-shell structured metal-based composite powders by electrostatic self-assembly. Background Art

[0002] Metal matrix composites use metal as the matrix. By adding one or more zero-dimensional particles, one-dimensional linear materials or two-dimensional lamellar materials with high-strength and high-modulus reinforcement phases, the metal matrix can not only retain the physical and chemical properties of the original metal, but also associate the performance of the reinforcement phase with the metal matrix, thereby obtaining better performance than the original metal matrix, thereby obtaining better composite materials and meeting more stringent service requirements.

[0003] In current powder metallurgy or 3D printing powders, alloy element powders and reinforcement phases have problems such as uneven distribution, easy agglomeration, and easy destruction of the reinforcement phase structure. The key lies in the preparation of powders. At present, composite powders prepared by powder metallurgy or 3D printing powders are generally obtained by mechanical mixing. Due to the differences in particle size, density, etc. between the reinforcement phase and alloy powder and the metal matrix, and more importantly, the agglomeration of the nanoscale coating layer material due to van der Waals force, it is impossible to achieve uniform distribution of the coating layer reinforcement phase on the surface of the metal powder. The composite powder prepared by the traditional mechanical mixing method belongs to a mixed composite powder. The mixed composite powder generally uses external force, such as centrifugation, stirring and impact, to make one particle distributed between another particle. It has problems such as local unevenness and weak binding force between different particles. Coated composite powders have attracted widespread attention due to their excellent properties. Coated composite powders are divided into particle embedded coating, layer coating and particle deposition coating according to the morphology of the coating layer. In the early days, powder coating was used as a surface modification technology to solve the dispersion and agglomeration problems of nanopowders. As research continued to deepen, it was found that there were also technical limitations in the preparation of coated composite powders. Rare earth compounds, metal elements and non-metal elements could not be directly coated by traditional gas or liquid coating methods.

[0004] Electrostatic self-assembly technology is an emerging method for synthesizing core-shell functional materials and biomolecules using cation-anion or zwitterion interactions. Usually, the synthesis reaction occurs in polar solvents or aqueous solutions, where the strong van der Waals forces of nanoparticles can be overcome to achieve uniform dispersion. Therefore, electrostatic self-assembly provides a promising way to prepare core-shell structured composite powders. In addition, the use of solid-liquid fluidized bed technology, taking advantage of the unique flow characteristics of fluidized powders, improves the problem of uneven dispersion on the coating powder and the coated powder. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a core-shell structure metal-based composite powder by electrostatic self-assembly. In view of the problems of poor dispersion uniformity and uneven coating of traditional coating layer powder materials, the present invention adopts electrostatic self-assembly technology combined with a solid-liquid fluidized bed for powder coating to prepare a new type of core-shell structure metal-based composite powder, and the composite powder has the advantages of high metal powder structural integrity, uniform coating layer powder distribution and low impurity content of the composite powder. The preparation method breaks through the technical bottleneck of high-quality core-shell structure metal-based composite powder preparation, and solves the problems of low powder integrity, easy destruction of coating powder structure, and impurity pollution in core-shell structure metal-based composite powder. The powder can be directly used as a powder raw material for sintering coated powder to reinforce different alloys, but its application is not limited to this.

[0006] To achieve the above object, the specific technical solutions of the present invention are as follows:

[0007] A method for preparing a core-shell structured metal-based composite powder by electrostatic self-assembly, comprising the following steps:

[0008] (1) The coating layer powder is modified by a surfactant so that its surface has a charge opposite to that of the metal powder, thereby obtaining a dispersed coating layer powder dispersion;

[0009] (2) placing the coating layer powder dispersion in a solid-liquid fluidized bed and making the liquid in a fluidized state, adding the metal powder into the fluidized bed and using the electrostatic self-assembly technology to make the coating material uniformly coated on the surface of the metal powder, the fluidization time is 5 to 240 minutes, and after fluidization, the core-shell structure metal-based composite powder is cleaned, dried, and packaged for use.

[0010] Specifically, a method for preparing a core-shell structured metal-based composite powder by electrostatic self-assembly, the method comprising the following steps:

[0011] 1) Preparation of surfactant modified solution

[0012] Weigh a certain mass of surfactant in a beaker, add deionized water, and use a heating device to accelerate the dissolution rate of the surfactant in water. After complete dissolution, a modified solution is obtained;

[0013] 2) Coating layer powder dispersion and surface modification

[0014] A certain mass of coating layer powder is added to the modified solution in step 1), and after ultrasonic treatment and stirring, a well-dispersed modified coating layer powder dispersion is obtained.

[0015] 3) Construction of solid-liquid fluidized bed and electrostatic self-assembly adsorption experiment

[0016] The solid-liquid fluidized bed device consists of a fluidized bed body, a sieve plate, a liquid inlet and outlet, a connecting hose, and a power mixing device for a speed-controlled peristaltic pump. The modified coating layer powder dispersion is loaded into the fluidized bed body, and the modified coating layer powder is moved in the fluidized bed by controlling the speed of the peristaltic pump. After a period of time, the metal powder is poured into the fluidized bed and begins to contact and combine with the coating layer powder. The core-shell structure metal-based composite powder is obtained through electrostatic self-assembly technology. After the assembly is completed, the powder is taken out, washed and dried for standby use.

[0017] Preferably, the main function of the surfactant used in step (1) is to disperse the coating layer powder and change the surface charge of the coating layer powder. The use standard of the surfactant is to select a suitable surfactant based on the characteristics of the surface charge distribution of the metal powder so that the surface of the coating layer powder has opposite charges and is evenly dispersed in the solution.

[0018] The composite powder described in the present invention is based on a metal base or a metal base alloy, and the coating layer powder material accounts for more than 0.05wt.% of the total weight of the composite powder. The coating layer powder uniformly coated on the surface of the metal powder includes but is not limited to one or more of carbides, rare earth compounds, metal oxides, non-metallic elements, metal elements and the like. At the same time, the coating layer content can be precisely controlled to be no less than 0.05wt.%.

[0019] Preferably, the coating layer powder includes, but is not limited to, one or more of carbides, rare earth compounds, metal oxides, non-metallic elements, metallic elements and the like as main components.

[0020] Further preferably, the metal powder is one or at least two of titanium powder, Ti-Fe alloy powder, Ti-Al alloy powder, Ti-Ni alloy powder, aluminum powder, copper powder, aluminum alloy powder, and copper alloy powder.

[0021] Preferably, the metal powder includes but is not limited to one of titanium alloy powder, aluminum alloy powder and copper alloy powder prepared by hydrogenation-dehydrogenation method or atomization method, with a particle size distribution of 5 to 150 μm and a powder addition amount of 5 to 200 g.

[0022] Preferably, the surfactant includes, but is not limited to, one or at least two of cetyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate, polyvinyl alcohol (PVA), and polyvinylpyrrolidone (PVP).

[0023] Preferably, the mass concentration of the surfactant is 0.1% to 10%. That is, the mass concentration of the surfactant-modified solution is 0.1% to 10%. Preferably, the solid-liquid fluidized bed device is composed of a fluidized bed, a sieve plate, a liquid inlet and outlet, a connecting hose, and a mixing device for a speed-regulating peristaltic pump, which is a conventional device in the art.

[0024] Further preferably, the solid-liquid fluidized bed has a cone-shaped distribution as a whole, with a volume of 500-1500 mL, and the liquid inlet and the liquid outlet are respectively at the lower end and the upper end of the bed and are at a certain distance from the two ends, about 3-5 cm.

[0025] Preferably, the pore size distribution of the sieve plates in the solid-liquid fluidized bed is 10-200 μm, and the speed of the speed-adjustable peristaltic pump is 20-150 rpm.

[0026] Preferably, the reaction time in the solid-liquid fluidized bed is related to the content of the adsorbed coating layer powder material, and the general fluidization time is 5 to 240 minutes.

[0027] Preferably, ethanol is generally added to the composite powder for washing, in order to wash away excess surfactant so as not to affect the subsequent sintering structure.

[0028] Preferably, the composite powder is dried by vacuum drying, the vacuum drying temperature is 40-80° C., and the drying time is longer than 2 hours.

[0029] The present invention uses a solid-liquid fluidized bed with the help of electrostatic self-assembly technology to comprehensively construct a uniformly coated composite powder with a core-shell structure, while maintaining the original structure of the powder, uniformly introducing a coating layer powder material with high structural integrity. Specifically, a surfactant is used to introduce hydrophilic groups on the surface of the coating layer powder material to modify the surface charge, thereby improving its hydrophilicity and ensuring the surface bonding force with the powder. At the same time, based on the high dynamic flow characteristics of the solid-liquid fluidized bed, it is ensured that the coating layer powder material is uniformly coated on the powder surface. The high heat transfer and conduction characteristics of the fluidized bed are utilized to remove the surface groups at high temperature to avoid component contamination. At the same time, the dynamic flow characteristics of the fluidized bed also ensure the uniform reduction of the surface groups of the coating layer powder material, avoiding the influence of impurities on the alloy performance, and preparing a metal-based composite powder with a uniform coating layer powder material, which provides a technical guarantee for the development of powder metallurgy or 3D printing to manufacture high-performance metal-based composite materials.

[0030] Compared with the traditional mechanical mixing technology for preparing core-shell structure metal-based composite powders, the advantages of the present invention are:

[0031] The coated powder material coated metal-based composite powder prepared by the present invention has the characteristics of strong powder coating, high integrity, and low impurity content; the coated powder material is evenly distributed on the surface of the metal-based powder, has strong bonding with the matrix, is not easy to fall off, and has a complete structure and is not easy to be damaged. The present invention is mainly achieved by combining the surface treatment of the coated powder material with a liquid phase mixing method and a gas phase heating and impurity removal technology. Compared with the traditional mechanical mixing technology, the technical process is simple, the required content of the coated powder material is low, the cost is low, and it is easy to achieve large-scale production, and the industrialization prospect is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the LaB6-coated Ti hydrogenation-dehydrogenation composite powder in Example 1 of the present invention;

[0033] Figure 2 This is a SEM image of graphene oxide coated Al composite powder in Example 2 of the present invention;

[0034] Figure 3 This is a high-magnification SEM image of the graphene oxide-coated Al composite powder in Example 2 of the present invention;

[0035] Figure 4 This is a SEM image of the graphene oxide-coated Ti composite powder in Example 2 of the present invention;

[0036] Figure 5 This is a high-magnification SEM image of graphene oxide on the surface of the graphene oxide-coated Ti composite powder in Example 2 of the present invention;

[0037] Figure 6 This is the SEM image of the graphene-coated Cu composite powder in Example 3;

[0038] Figure 7 This is the SEM image of the Si powder coated Ti-Fe composite powder in Example 4;

[0039] Figure 8 This is the SEM image of the boron powder coated Ti-6Al-4V composite powder in Example 5. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0041] Example 1

[0042] 1) Prepare CTAB solution: weigh 0.5-5 g of CTAB, add 500 mL of deionized water, and heat at 60-80°C to completely dissolve it.

[0043] 2) Weigh 5-10 g of LaB6 particles and add them to the solution in 1), ultrasonicate for 10-30 min, and then stir for 2-4 h to obtain a LaB6 dispersion with a positive charge.

[0044] 3) placing the positively charged LaB6 dispersion in 2) in a solid-liquid fluidized bed, connecting the liquid outlet-peristaltic pump control system-liquid inlet device through a silicone tube, then weighing 5-200g of Ti powder and adding it into the solid-liquid fluidized bed, and making the liquid in a fluidized state, the speed of the peristaltic pump is 20-150rpm, and the mixing time is 5-240min;

[0045] 4) After the mixing is completed, the coated composite powder in the solid-liquid fluidized bed of 3) is taken out, and the obtained composite powder is placed in a vacuum oven at 30-80°C for drying for 2-6 hours to obtain Ti powder coated with LaB6;

[0046] Figure 1 This is the SEM image of the LaB6-coated Ti hydrogenation-dehydrogenation composite powder in Example 1. The main component of the coating layer on the surface of the powder is LaB6, which is evenly distributed.

[0047] Example 2

[0048] The difference between the present embodiment 2 and the embodiment 1 is that the metal powder is aluminum powder or titanium powder, the coating layer powder material is graphene oxide, and the surfactant is sodium dodecylbenzene sulfonate or polyvinyl alcohol.

[0049] Figure 2 This is the SEM image of the graphene oxide coated Al composite powder in Example 2;

[0050] Figure 3 This is a high-magnification SEM image of the graphene oxide-coated Al composite powder in Example 2, and the graphene oxide is evenly distributed on the surface of the metal powder;

[0051] Figure 4 This is the SEM image of the graphene oxide coated Ti composite powder in Example 2;

[0052] Figure 5 This is a high-magnification SEM image of graphene oxide on the surface of the graphene oxide-coated Ti composite powder in Example 2. The graphene oxide is distributed relatively evenly on the surface of the metal powder.

[0053] Example 3

[0054] The difference between the present embodiment 3 and the embodiment 1 is that the metal powder is changed to copper powder, and the coating layer powder material is graphene.

[0055] Figure 6 This is the SEM image of the graphene-coated Cu composite powder in Example 3. The graphene sheets are evenly coated on the surface of the Cu composite powder, and the lamellar graphene can be clearly distinguished.

[0056] Example 4

[0057] The difference between Example 4 and Example 1 is that the metal powder is changed to Ti-Fe composite powder, and the coating layer powder material is Si powder.

[0058] Figure 7 This is a SEM image of the Si powder coated Ti-Fe composite powder in Example 4. Si nanoparticles are coated on the surface of the Ti-Fe composite powder to achieve uniform coating in the fluidized bed after modification.

[0059] Example 5

[0060] The difference between Example 5 and Example 1 is that the metal powder is changed to Ti-6Al-4V powder, and the coating layer powder material is boron powder. The specific steps are as follows:

[0061] Weigh 45-80 g of NaOH and add it to 800 mL of deionized water, then add 3-5 g of boron powder and heat and stir at 60-80° C. for 4 hours. Centrifuge after cooling, wash with deionized water to neutrality, and then disperse in 500 mL of deionized water to obtain a negatively charged boron powder dispersion.

[0062] Then, according to the steps in Example 1, the coated composite powder was obtained by electrostatic self-assembly technology in a solid-liquid fluidized bed.

[0063] Figure 8 This is a SEM image of the boron powder coated Ti-6Al-4V composite powder in Example 5. The boron nanoparticles are evenly coated on the surface of the Ti-6Al-4V composite powder.

[0064] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.

[0065] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a core-shell structured metal-based composite powder by electrostatic self-assembly, the method comprising the following steps: (1) The coating layer powder is modified by a surfactant so that its surface has a charge opposite to that of the metal powder, thereby obtaining a dispersed coating layer powder dispersion; (2) placing the coating layer powder dispersion in a solid-liquid fluidized bed and making the liquid in a fluidized state, adding the metal powder into the fluidized bed to make the coating material uniformly coated on the surface of the metal powder by electrostatic self-assembly, the fluidization time is 5 to 240 minutes, and after fluidization, the core-shell structure metal-based composite powder is cleaned, dried, and packaged for use.

2. The method according to claim 1, characterized in that In step (1), the surfactant includes, but is not limited to, one or at least two of cetyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, polyvinyl alcohol, and polyvinyl pyrrolidone.

3. The method according to claim 1, characterized in that The mass concentration of the surfactant is 0.1% to 10%.

4. The method according to claim 1, characterized in that: The coating layer powder is one or at least two of LaB6, graphene oxide, graphene, Si powder and boron powder.

5. The method according to claim 1, characterized in that The metal powder is one or at least two of titanium powder, Ti-Fe alloy powder, Ti-Al alloy powder, Ti-Ni alloy powder, aluminum powder, copper powder, aluminum alloy powder and copper alloy powder, and has a particle size distribution of 5 to 150 μm.

6. The method according to claim 1, characterized in that The mass ratio of the coating layer powder to the metal powder is 1:(1-40).

7. The method according to claim 1, characterized in that In step (2), the drying temperature is 40-80° C. and the drying time is ≥2 h.

8. The method according to claim 1, characterized in that The solid-liquid fluidized bed comprises a solid-liquid fluidized bed body, a sieve plate, a liquid inlet, a liquid outlet, a connecting hose, and a speed-regulating peristaltic pump; the solid-liquid fluidized bed body as a whole presents a cone-shaped distribution, with a volume of 500 to 1500 mL, the liquid inlet and the liquid outlet are respectively arranged at the lower end and the upper end of the solid-liquid fluidized bed body and are 3 to 5 cm away from the two ends, the pore size distribution of the sieve plate in the solid-liquid fluidized bed is 10 to 200 μm, and the speed of the peristaltic pump is regulated to 20 to 150 rpm.

Citation Information

Patent Citations

  • Alloy powder, preparation method therefor, and use therefor

    CA3194475A1

  • Preparation method of 3D printing composite formed by coating alloy powder with graphene

    CN106825552A

  • Method for preparing metal soft magnetism powder core by utilizing SiO2 coated metal powder technology and metal soft magnetism powder core prepared through method

    CN107020373A

  • Insulating soft magnetic metal powder, preparation method thereof and magnetic powder core

    CN115620982A

  • Core-shell double-layer structure microsphere as well as preparation method and application thereof

    CN115873143A